Frozen Cuttlefish (Sepia officinalis) Production Process with Contact Plate Freezing Method at PT. Karya Mina Putra, Rembang, Central Java - Saltsa Arinda Putri; Laksmi Sulmartiwi (Journal of Marine and Coastal Science, 2021)
Cuttlefish is widely consumed by the public because it has a soft meat texture and high nutritional content. This makes the cuttlefish one of the mollusca that is a source of protein in addition to squid and octopus. The disadvantage of cuttlefish is that it is prone to deterioration in quality. One effort to prevent quality deterioration in cuttlefish is by freezing. The purpose of the implementation of this Field Work Practice is to decide the production process of frozen  cuttlefish  (Sepia officinalis) using the Contact Plate Freezing (CPF) method and to know the obstacles that occur in the production process. Field Work Practice was held in PT. Karya Mina Putra, Rembang, Central Java. The stages of the frozen cuttlefish  production  process  at  PT.  Mina Putra's work includes the reception of raw materials, weighing I and sorting, labeling I, weighing II, washing, pan preparation, freezing, glazing, packaging and labeling II, storing in cold storage, and loading. The freezing process is carried out by the Contact Plate Freezing (CPF) method for 6 hours until the temperature reaches -40 ° C. The obstacle in the production process of frozen cuttlefish is there was a Contact Plate Freezing (CPF) machine damage and there are some employees who do not apply the SOP applied to prevent cross-contamination of the product.